Mushroom as a Mechanism to Alleviate Poverty, Unemployment and Malnutrition - Shakil, Mohammad Hassan; Tasnia, Mashiyat; Munim, Ziaul Haque; Mehedi, Md. Humayun Kabir (Asian Business Review, 2014)
Mushroom is the most popular delicious, nutritious and medicinal vegetable in the world. Now it is considered as the most promising concept for crop diversification. It has been regarded as an effective means for poverty alleviation in less developed countries due to its potential for a quick, high return of profit on a small investment. Bangladesh is one of the most suitable countries in the world for Mushroom cultivation due to its favorable climate, cheap raw materials and labor cost and high market price. It is such an income generating concept that can alleviate poverty and eradicate malnutrition. It can also create employment opportunities for landless beggar, educated and uneducated youth, person with disabilities and adolescent men and women respectively. The primary objective of the study is to alleviate poverty, unemployment and malnutrition through cultivating and selling mushroom. The study is analytical and theoretical in nature and based on the secondary data. However, personal interview has been conducted to the mushroom farmers to depict the cost and profitability of Mushroom cultivation. The study finds that Mushroom cultivation can open a new opportunity for landless and unemployed people as it does not require any cultivable land and can be grown in a room by racking vertically. One can earn nearly TK 4-5 thousands a month by investing only TK 10-15 thousands. So, it is possible to make a handsome profit by investing a small amount of capital and labor in Mushroom cultivation.